Glomuvenous malformations with smooth muscle and eccrine glands: unusual histopathologic features in a familial setting. (20th January 2014) - Borroni, Riccardo G.; Grassi, Sara; Concardi, Monica; Puccio, Ignazio; Giordano, Calogero; Agozzino, Manuela; Caspani, Clelia; Grasso, Maurizia; Diegoli, Marta; Arbustini, Eloisa
<x xml:space="preserve">Abstract</x> Glomuvenous malformations (OMIM 138000) are hamartomas presenting in childhood as multiple, bluish papules and nodules in the skin, which are characterized histopathologically by irregular vascular spaces surrounded by typical glomus cells. Glomuvenous malformations are caused by autosomal dominant mutations of the GLMN gene. A 34‐year‐old woman and her 16‐year‐old son presented with bluish papules and nodules since childhood. Biopsy specimens from both patients showed histopathologic features of glomuvenous malformations, unusually in consistent and close association with smooth muscle, hair follicles and eccrine glands. Sequencing of the GLMN gene revealed the p.C36X (c.108C>A) mutation in germline DNA from both patients. This is probably the first report describing the hamartomatous features of familial glomuvenous malformations consistently associated with a prominent smooth muscle component and eccrine glands.